Evaluation of a Coupled Snow and Energy Balance Model for Zhadang Glacier, Tibetan Plateau, Using Glaciological Measurements and Time-Lapse Photography - Huintjes, Eva; Sauter, Tobias; Schroter, Benjamin; Maussion, Fabien; Yang, Wei; Kropaček, Jan; Buchroithner, Manfred; Scherer, Dieter; Kang, Shichang; Schneider, Christoph (Arctic, Antarctic, and Alpine Research, 2015)
We present a new open-source, collaborative "COupled Snowpack and Ice surface energy and MAss balance model" (COSIMA) that is evaluated for Zhadang glacier, Tibetan Plateau. The model is calibrated, run, and validated based on in situ measurements and atmospheric model data from the High Asia Refined analysis (HAR) over the period April 2009 to June 2012. Results for the model runs forced by both in situ measurements and HAR agree well with observations of various atmospheric, glaciological, surface, and subsurface parameters on the glacier. A time-lapse camera system next to the glacier provides a 3-year image time series of the mean transient snow line altitude and the snow cover pattern, which is used for the spatial and temporal validation of the model. The model output corresponds very well to the observed temporal and spatial snow cover variability. The model is then run for a 10-year period of October 2001 to September 2011 forced with HAR data. In general, the radiation components dominate the overall energy turnover (65%), followed by the turbulent fluxes (31%). The generally dry atmosphere on the Tibetan Plateau causes sublimation to be responsible for 26% of the total mass loss. A proportion of 11% of the surface and subsurface melt refreezes within the snowpack.